Outcome in Patients Treated with Intra-arterial thrombectomy: The optiMAL Blood Pressure control (OPTIMAL-BP) Trial. Issue 8 (October 2022) - Nam, Hyo Suk; Kim, Young Dae; Choi, Jin Kyo; Baik, Minyoul; Kim, Byung Moon; Kim, Dong Joon; Heo, JoonNyung; Shin, Dong Hoon; Lee, Kyung-Yul; Jung, Yo Han; Baek, Jang-Hyun; Hwang, Yang-Ha; et al.
Rationale: Very early stage blood pressure (BP) levels may affect outcome in stroke patients who have successfully undergone recanalization following intra-arterial treatment, but the optimal target of BP management remains uncertain. Aim: We hypothesized that the clinical outcome after intensive BP-lowering is superior to conventional BP control after successful recanalization by intra-arterial treatment. Sample-size estimates: We aim to randomize 668 patients (334 per arm), 1:1. Methods and design: We initiated a multicenter, prospective, randomized, open-label trial with a blinded end-point assessment (PROBE) design. After successful recanalization (thrombolysis in cerebral infarction score ≥ 2 b), patients with elevated systolic BP level, deﬁned as the mean of two readings ≥ 140 mmHg, will be randomly assigned to the intensive BP-lowering (systolic BP < 140 mm Hg) group or the conventional BP-lowering (systolic BP, 140−180 mm Hg) group. Study outcomes: The primary efficacy outcomes are from dichotomized analysis of modified Rankin Scale (mRS) scores at three months (mRS scores: 0–2 vs. 3–6). The primary safety outcomes are symptomatic intracerebral hemorrhage and death within three months. Discussion: The OPTIMAL-BP trial will provide evidence for the effectiveness of active BP control to achieve systolic BP < 140 mmHg during 24 h in patients with successful recanalization after intra-arterial treatment. Clinical trial registration: ClinicalTrials.gov Identifier: NCT04205305.